Small choroidal melanoma – a diagnostic problems - Romanowska-Dixon, Bożena; Kubicka-Trząska, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
The aim of this paper is to present the most common diagnostic problem associated with a small choroidal melanoma. In some cases other lesions such as a choroidal naevus, an exudative type of age related macular degeneration (AMD) with the presence of subretinal haemmorrhage, retinal pigment hypertrophy, choroidal haemangioma and choroidal metastatic tumours may mimic small choroidal melanomas. Based on the literature and on our own experience we present the basic clinical features of these lesions, their characteristic fluorescein angiography, indocyanine green angiography and ultrasonography pictures that can be helpful in differential diagnosis.